Auricular acupoint therapy for functional gastrointestinal disorders: a systematic review and meta-analysis of randomized clinical trials - Meng-Yuan Shen; Ze-Jiong Li; Shu-Han Wang; Tian-Chen Lin; Qin-Yi Lou; Shan Liu; Dan-Dan Feng; Dong-Dong Yang; Chen-Juan Wang; Zhe-Kai Ying; Rong Zhou; Jian-Nong Wu (Frontiers in Medicine)
IntroductionThis study aims to conduct a systematic review and meta-analysis of randomized controlled trials to evaluate the efficacy and safety of auricular acupoint therapy (AAT) for functional gastrointestinal disorders (FGIDs).MethodsWe conducted a thorough search across eight databases, including PubMed, EMBASE, Web of Science, the Cochrane Library, CNKI, Wanfang, VIP, and CBM. The search covered the period from the inception of each database up to June 30, 2024. The authors independently reviewed all the references, evaluated the risk of bias, and extracted the data. GRADEpro software was utilized to calculate overall strength of evidence. A random effects or fixed effects model was selected on the basis of the p-value and I2. RevMan 5.3, Stata/MP 18.0, R 4.3.1 and R Studio 2023.09.0 were used for data processing. TSA 0.9.5.10 beta software was used to evaluate data stability.ResultsThe review included 19 randomized controlled trials with a total of 1,681 patients (895 in the treatment group and 886 in the control group). The treatment duration ranged from 2–12 weeks. The meta-analysis revealed that, compared with the control, AAT was significantly more effective at treating FGIDs (RR: 1.35; 95% CI: 1.21–1.51; p < 0.001), reducing the symptom score (MD: −1.94; 95% CI: −3.06 to −0.85; p < 0.001; five trials), improving the SAS score (MD: −12.47; 95% CI: −13.92 to −11.01; p < 0.001; five trials), and improving the SDS score (MD: −4.97; 95% CI: −9.23 to −0.72; p = 0.02; six trials). A total of two articles mentioned relatively significant adverse reactions (MD: 2.98; 95% CI: 0.51–17.26; p = 0.009). Sensitivity and trial sequential analyses confirmed the stability of these results.DiscussionWhile our meta-analysis suggests that AAT may offer benefits for FGIDs, these results must be interpreted with caution due to methodological limitations in the included trials. Further investigations in high-quality trials are warranted.Systematic review registrationhttps://clinicaltrials.gov/, identifier CRD42024558786.